Management of gunshot Injuries of the Extremities – An Update - Qadir, Raja Irfan; Ahmed, Jamil (Journal of Postgraduate Medical Institute, 2011)
Gunshot injuries are more common in NWFP as compared to other province of Pakistan. With the start of Afghan Jehad and influx of more than 35 million Afghan Refugees into Pakistan NWFP has become a big market for Firearms. More than a 100 factories are manufacturing arms here, including replicas of latest Soviet assault rifles.